Pan-genome analysis of wax apple (Syzygium samarangense) and its association with fruit size and cold tolerance - Long, Xing; Li, Liang; Fang, Ren; Zhang, Ji; Zhou, Ping; An, Zhenyu; Tang, Wenzhong; Yao, Jinyan; Wei, Xiuqing (Frontiers in Plant Science, 2026)
IntroductionWax apple (Syzygium samarangense) is a tropical fruit crop of high economic value, in which fruit size and cold tolerance are key traits affecting cultivation range and market quality. However, the genetic basis underlying these traits remains poorly understood at the genome-wide level.MethodsWe constructed the first wax apple pangenome using whole-genome resequencing data from 27 accessions. Novel non-redundant sequences were identified and annotated, and genes were classified based on presence/absence variation (PAV). Population structure was inferred using both PAV and single-nucleotide polymorphism (SNP) data. Structural variants (SVs) were detected genome-wide, and candidate genes associated with fruit size and cold tolerance were identified by integrating PAV, SNP-based XP-CLR, and SV-based F_ST analyses.ResultsThe pangenome contained 69 Mb of novel non-redundant sequences and 707 newly predicted genes. PAV analysis classified 35,468 genes as core, 10,789 as dispensable, and 364 as private. Population structure analyses consistently divided the accessions into three subgroups, indicating a multi-lineage domestication history. We identified 44,567 SVs, including 9,999 duplications, 34,593 deletions, and 65 insertions. Integrative selective sweep analyses revealed candidate genes associated with fruit size and cold tolerance. An S-adenosylmethionine-dependent methyltransferase gene was located within a cold-tolerance-related selective sweep region. Genes from the Mol family, as well as genes involved in abscisic acid metabolism and quercetin 3′-O-glucosyltransferase activity, were significantly enriched in large-fruited accessions. Additionally, SVs showed strong genetic differentiation in diterpene phytoalexin biosynthesis genes among cold-tolerant lines.DiscussionThis study provides the first pangenome resource for wax apple and reveals extensive genomic variation associated with key agronomic traits. The identified candidate genes and structural variants offer insights into the genetic mechanisms underlying fruit size and cold tolerance and provide a genomic foundation for trait improvement and molecular breeding of wax apple.